The Chasmic Concept of Space Vector Pulse Width Modulation - Shivam Singh; Satyam S. Choudhary, Omkar P. Durgavale, Shahuraj S. Sable (Journal of Power Electronics and Devices, 2021)
Many smartly engineered techniques exist when it comes to inverter switching. Every technique holds its specialty, yet this project will focus on the best of them all. Applications of inverters face three major requirements and limitations which are: 1) harmonic contents 2) best utilization of DC-link voltage 3) the switching frequency. Space Vector Pulse Width Modulation technique has undeniable prominence due to the advantages it has over all others. SVPWM is a special switching scheme of the six power semiconductor switches of a three-phase power converter. The popularity of this technique in applications such as control of induction and permanent magnet synchronous motors has baffled the industrial circumference. In this brilliantly established technique, the drawbacks of other prescribed methodologies are improved drastically. SVPWM provides a constant switching frequency and therefore the switching frequency could be easily adjusted. The harmonic generation here is quite less comparatively. Even though SVPWM is more complicated than the preceding techniques, it overshadows all of them. This paper will establish a conceptual premise towards a deeper understanding of this technique.